The frequency of metabolic syndrome in patients with the subclinical hypothyroidism - Mulić Mersudin; Skrijeljm Fadil; Hajrović Šefcet; Prelević Rade; Milev Boško (Vojnosanitetski Pregled)
Background/Aim. An increased cardiovascular risk of thyroid dysfunction is associated with the impairment of lipid and lipoprotein metabolism, endothelial dysfunction, metabolic, hormonal, hemodynamic changes and coagulation disorders. Subclinical hypothyroidism is characterized by supernormal thyroid-stimulating hormone (TSH) level along with normal values of thyroid hormones. The association of subclinical hypothyroidism with higher cardiovascular risk has not been fully clarified. The aim of the study was to determine the frequency of metabolic syndrome and the associated cardiovascular risk factors in patients with the subclinical hypothyroidism. Method. The study included 140 subjects aged from 18 to 65 years, out of which 105 subjects had subclinical hypothyroidism and 35 subjects were the euthyroid controls. The clinical trial program, completed in all subjects, included: detailed medical history and physical examination, waist circumference, and laboratory tests [fasting glycemia, lipid and lipoprotein status, free triiodothyronine (FT3) and free thyroxine (FT4) and TSH levels]. Results. Out of 105 patients with the subclinical hypothyroidism, mean age 44.15 ± 11.23 years, 77 (73.3%) patients had metabolic syndrome. In the control group consisting of 35 subjects, mean age 33.80 ± 10.60 years, only 3 (8.6%) subjects had metabolic syndrome. Mean values of the waist circumference, fasting glycemia, triglycerides, systolic and diastolic blood pressure were higher in subclinical hypothyroidism group in relation to the controls (p < 0.0001). Mean value of high-density lipoprotein (HDL) cholesterol was lower in subclinical hypothyroidism group as compared to the controls (p < 0.002). Conclusion. The frequency of metabolic syndrome was 9 times higher in subjects with the subclinical hypothyroidism in relation to subjects without any subclinical hypothyroidism.